2018
DOI: 10.1001/jamaneurol.2017.3890
|View full text |Cite
|
Sign up to set email alerts
|

Association of Visual Impairment in Neuromyelitis Optica Spectrum Disorder With Visual Network Reorganization

Abstract: IMPORTANCE Severe visual impairment is one of the major symptoms in neuromyelitis optica spectrum disorder (NMOSD), but functional network reorganization induced by the diminished sensory input has not been investigated thus far. OBJECTIVE To examine adaptive visual network connectivity changes in NMOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The optic radiation (OR) is an integral part of the afferent visual system and belongs to the most frequently affected white matter pathways in autoimmune neuroinflammatory disorders of the central nervous system, i.e. multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD) ( Backner et al, 2018 ; Balcer et al, 2015 ; Bennett et al, 2015 ; Finke et al, 2018 ; Martínez-Lapiscina et al, 2014 ; Pache et al, 2016a , Pache et al, 2016b ; Pache et al, 2016a , Pache et al, 2016b ; Petzold et al, 2014 ; Pfueller and Paul, 2011 ; Scheel et al, 2014 ; Schmidt et al, 2017 ; Sinnecker et al, 2015b ; Wingerchuk et al, 2015 ). Diffusion-weighted magnetic resonance imaging (DW-MRI) yields the potential to non-invasively investigate microstructural OR integrity ( Assaf and Pasternak, 2008 ; Filippi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The optic radiation (OR) is an integral part of the afferent visual system and belongs to the most frequently affected white matter pathways in autoimmune neuroinflammatory disorders of the central nervous system, i.e. multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD) ( Backner et al, 2018 ; Balcer et al, 2015 ; Bennett et al, 2015 ; Finke et al, 2018 ; Martínez-Lapiscina et al, 2014 ; Pache et al, 2016a , Pache et al, 2016b ; Pache et al, 2016a , Pache et al, 2016b ; Petzold et al, 2014 ; Pfueller and Paul, 2011 ; Scheel et al, 2014 ; Schmidt et al, 2017 ; Sinnecker et al, 2015b ; Wingerchuk et al, 2015 ). Diffusion-weighted magnetic resonance imaging (DW-MRI) yields the potential to non-invasively investigate microstructural OR integrity ( Assaf and Pasternak, 2008 ; Filippi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…43,45 A study focusing on the visual system of patients with NMOSD and previous ON has shown increase in the functional connectivity of the primary visual network compared with those without ON. 11 These findings were also associated with greater retinal damage and reduced visual acuity, suggesting an attempt at cortical reorganization. Similar findings were seen in our previous work, showing an increase in visual network connectivity in patients with CIS-ON compared with CIS-nON.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, our previous works have emphasized the importance of activity along the visual dorsal stream in patients with ON, 6-10 but our works on connectivity have used wholenetwork resolution. 10,11 Therefore, to examine whether there are specific connectivity changes within the visual network, we herein used graph theory methods, 12,13 focusing on its regional measures to pinpoint which visual regions are more affected.…”
mentioning
confidence: 99%
“…Using fMRI, Rocca et al (2004) showed an irregular form of movement associated with cortical activation in patients with NMOSD that extended beyond the sensorimotor network and involved the visual network of the brain. Previous studies (Lopes et al, 2015;Cai et al, 2017) have also explored visual cortex FC in NMOSD but did not give an account on its association with the clinical data such as their disease duration or frequency of optic neuritis attack; two previous reports (Lopes et al, 2015;Finke et al, 2018) used the activation fMRI approach and showed increased connectivity in NMOSD patients when compared to healthy controls. Cai et al (2017) used the seed-based approach, similar to our current approach, and showed decreased connectivity in the higher visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time series from all of the voxels within the ROI was used as the seed reference time series, and the Pearson's correlation coefficient (between the average time series for that seed and each voxel in the brain) was computed as the strength of FC. For further statistical analysis, the correlation coefficients were transformed to z-values using the Fisher r-to-z transformation to improve the normality of the correlation coefficients (Finke et al, 2018). Thus, a map that represented the FC strength and the seed region (in terms of the z-values for each subject) was obtained.…”
Section: Mri Data Preprocessingmentioning
confidence: 99%